THE INFLUENCE OF GRAPHITE FILLERS ON THE EFFICIENCY OF INTUMESCENT FIRE PROTECTION COATINGS - TARAN, NADIA; SHOLOGON, VICTOR; VAKHITOV, RAMIL; KALAFAT, KOSTYANTIN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Ensuring the fire resistance of building structures is a key aspect of fire safety aimed at maintaining their load-bearing capacity when exposed to high temperatures. This is achieved through the use of fire protection coatings that slow down the heating of structures to critical temperatures, which provides time for evacuation and rescue operations. Despite the availability of a wide range of fire-resistant materials, the issue of developing new coatings with improved performance, environmental and technical characteristics remains relevant. Current research is focused on the creation of intumescent systems with increased efficiency, reduced thickness of the protective layer and the use of environmentally friendly components. Intumescent fire protection coatings are an effective means of improving the fire safety of building structures, which operate on the principle of forming a protective foam-char layer when exposed to high temperatures. One of the key areas of improvement of such coatings is the use of graphite fillers, in particular thermally expandable graphite (EG) and swollen graphite (SG), to optimise their heat resistance and mechanical strength. The aim of this study is to determine the effect of graphite fillers on the swelling efficiency of intumescent coatings by evaluating the volume coefficient of swelling and mass loss. The influence of varying the composition of the ingredients of the fire protection system based on ammonium polyphosphate, melamine, pentaerythritol and ethylene vinyl acetate was studied. The research results show that EG provides intensive swelling, forming a protective layer with low thermal conductivity, but its use in pure form provokes the creation of an irregular loose structure of the char residue and a decrease in adhesion to the protected surface. At the same time, SG stabilises the char structure, improving its mechanical characteristics, but does not contribute to active gas formation. Graphite fillers interact with other components of the intumescent system, which affects the swelling mechanisms and stability of the protective layer. The study confirms the efficiency of graphite fillers in intumescent coatings and their significant potential for improving reactive fire protection systems. The results obtained can be recommended for determining the optimal formulation of intumescent coatings on an inorganic substrate for the development of roll materials for fire protection of steel and wooden structures and cable communications. Further work may focus on determining the optimal concentrations of EG and SG to achieve the maximum level of fire protection and environmental safety of the coatings.